Does social work really want to dance with zombies? A reply to Lynch and Wilson - Stephen A. Webb (Social Work and Society)
This reply to Lynch and Wilson's recent publication in this journal is a modest contribution which involves an intermingling of criticism and confirmation with a potted history of right-wing luminaries such as J.M. Buchanan and Gary Becker tucked inside some meta-textural analysis of the Mont Pèlerin Society and the collective dynasty of neoliberalism. The authors place heavy emphasis on the"dichotomous" relationship between collectivism and economic liberalism and suggest that the unresolved tensions impede a critical social work. Rather than offering a"third way" between communitarianism and liberalism, this reply breaks open the debate by changing terrain to post-anarchism and Jean-Luc Nancy's social ontology as a more contemporary reading for the politics of critical social work. By tying the concepts of"freedom" to"community" together in a non-substantialist way, I argue that neither neoliberalism, nor normative versions of community are viable antidotes to zombie economics and our political futures. An alternative account of Agamben's destituent politics of community for social work is elaborated through an engagement with post-anarchist writings of Marcello Tarì and The Invisible Committee.